Reference values for spirometry, including vital capacity, in Japanese adults calculated with the LMS method and compared with previous values - Kubota, Masaru; Kobayashi, Hirosuke; Quanjer, Philip H.; Omori, Hisamitsu; Tatsumi, Koichiro; Kanazawa, Minoru (Respiratory investigation, 2014)
Reference values for lung function tests should be periodically updated because of birth cohort effects and improved technology. This study updates the spirometric reference values, including vital capacity (VC), for Japanese adults and compares the new reference values with previous Japanese reference values. Spirometric data from healthy non-smokers (20,341 individuals aged 17–95 years, 67% females) were collected from 12 centers across Japan, and reference equations were derived using the LMS method. This method incorporates modeling skewness (lambda: L), mean (mu: M), and coefficient of variation (sigma: S), which are functions of sex, age, and height. In addition, the age-specific lower limits of normal (LLN) were calculated. Spirometric reference values for the 17–95-year age range and the age-dependent LLN for Japanese adults were derived. The new reference values for FEV1 in males are smaller, while those for VC and FVC in middle age and elderly males and those for FEV1, VC, and FVC in females are larger than the previous values. The LLN of the FEV1/FVC for females is larger than previous values. The FVC is significantly smaller than the VC in the elderly. The new reference values faithfully reflect spirometric indices and provide an age-specific LLN for the 17–95-year age range, enabling improved diagnostic accuracy. Compared with previous prediction equations, they more accurately reflect the transition in pulmonary function during young adulthood. In elderly subjects, the FVC reference values are not interchangeable with the VC values.